Multimodal retinal imaging in the diagnosis of intraretinal microvascular abnormality. (1st November 2016) - Okada, Mali; Cardoso, Joāo Nobre; Sim, Dawn; Egan, Catherine A.; Ahmed, Shahee; Tufail, Adnan
ABSTRACT: Introduction : Retinal imaging in diabetic retinopathy has experienced significant advances since the days of the Early Treatment for Diabetic Retinopathy Studies. Differentiating intraretinal microvascular abnormalities (IRMA) from neovascular complexes remain a challenging part of disease staging but may become easier in this age of multimodal imaging. Areas covered : This review presents an overview of the available imaging modalities, their current applications and limitations as well as future developments in the pipeline. The implication of new imaging technology on the traditional definition of IRMAs and how this may translate into potential treatment outcomes for the patient will be discussed. This review is based on a literature search of all English language articles published on PubMed. Expert commentary : The characterisation of IRMA has evolved with the development of OCT to identify morphological differences. Wide field imaging may also identify IRMA outside of standard field of view of conventional imaging. The use of advanced imaging techniques is likely to play a greater role in both disease staging and management of diabetic retinopathy in the future.